FACTORS AFFECTING THE FLOW TIME OF PRESENTATION OF FINANCIAL STATEMENTS - Wikan Budi Utami (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
This study aims to determine the factors that influence the time span of the presentation of financial statements on banking companies listed on the Indonesia Stock Exchange in 2016-2017. The factors that are suspected to influence the time span of the presentation of financial statements on banking companies listed on the Indonesia Stock Exchange in 2016-2017 in this study are solvency, profitability and company size. The sampling method uses a purposive sampling method of 52 sample banking companies. The results of this study indicate that solvency has no significant effect on the time span of financial statement presentation with a calculated value of 1.728 α = 0.05. Profitability has a significant effect on the time span of the presentation of financial statements with a significant value of 0.041 t table 2.00958. The size of the company has no significant effect on the time span of financial statement presentation with a significant level of 0.066> α = 0.05 and t count value 1.880 F table 3.18 and a significance value of 0.004